2018
DOI: 10.1002/ppul.23958
|View full text |Cite
|
Sign up to set email alerts
|

Growth trajectories and oxygen use in neuroendocrine cell hyperplasia of infancy

Abstract: NEHI is associated with substantial respiratory and extra-pulmonary morbidity. Failure to thrive may be associated with greater respiratory morbidity, though further studies are required to define this interaction. Determining the association of these comorbidities and respiratory course in NEHI may enable development of strategies to improve these modifiable factors and potentially pulmonary outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Clinical examination reveals retractions, fine crackles and failure to thrive. 1,6,8,10,11 Other diseases with similar clinical presentation must be ruled out, especially surfactant dysfunction disorders, pulmonary infections, primary ciliary dyskinesia, and cystic fibrosis. If a lung biopsy is performed, the tissue is typically characterized by (a) neuroendocrine cells (NEC) found in at least 75% of total airway profiles, (b) NEC representing at least 10% of epithelial airway profiles, and (c) large and/or numerous neuroepithelial bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examination reveals retractions, fine crackles and failure to thrive. 1,6,8,10,11 Other diseases with similar clinical presentation must be ruled out, especially surfactant dysfunction disorders, pulmonary infections, primary ciliary dyskinesia, and cystic fibrosis. If a lung biopsy is performed, the tissue is typically characterized by (a) neuroendocrine cells (NEC) found in at least 75% of total airway profiles, (b) NEC representing at least 10% of epithelial airway profiles, and (c) large and/or numerous neuroepithelial bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Infants with PTI typically present with tachypnea and hypoxemia in the first months of life. Clinical examination reveals retractions, fine crackles and failure to thrive 1,6,8,10,11 . Other diseases with similar clinical presentation must be ruled out, especially surfactant dysfunction disorders, pulmonary infections, primary ciliary dyskinesia, and cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, these sleep studies were performed in Denver, where the altitude may bias towards lower oxygen saturations. In a cohort of 42 children with NEHI, Nevel et al reported that 31 (74%) were diagnosed with failure to thrive at some point in their course, and its presence was associated with longer duration of oxygen supplementation. Time‐to‐event analysis showed 50% had daytime and nocturnal supplemental oxygen discontinued after 32 and 87.5 months of therapy, respectively.…”
Section: Rare Lung Diseasesmentioning
confidence: 99%
“…9 Patients usually present with frequent respiratory exacerbations, poor weight gain, sleep-related breathing disorders and the need for supplemental oxygen therapy. [10][11][12] Although clinical course is generally favorable, the long-term outcome has not yet been fully established. 7,13 To date, there are no reports available about this entity in our country.…”
mentioning
confidence: 99%